Bertiella sp. (Meyner, 1895) infection of Alouatta caraya (Humboldt, 1812) in urban and natural environments in Ñeembucú, southwest Paraguay. Issue 9 (29th June 2020) - Kane, John; Smith, Rebecca L.
Abstract: Bertiella sp., a cestode known to infect a variety of hosts, including nonhuman primates and humans, was identified in Paraguay as early as 1895, but no systematic analysis of wild primates' gastrointestinal parasites has ever been carried out in Paraguay. Increased urbanization in southwest Paraguay has pushed the Paraguayan howler monkey ( Alouatta caraya) into anthropogenic habitats, particularly in the city of Pilar (Ñeembucú department), giving rise to greater potential for zoonotic transmission between wild primates and humans. From July to December 2018, fecal samples were noninvasively collected from 48 howlers inside Pilar (urban environment), the Pilar Military Base (intermediate environment), and a ranch 27 km outside Pilar in the humid Chaco (natural environment) and analyzed for Bertiella eggs and proglottids using macro‐analysis and formol‐ether sedimentation. Howlers living in the urban environment had the highest rates of Bertiella infection (50% prevalence), with considerably lower infection rates in the intermediate environment (6.25% prevalence) and natural habitats (0% prevalence). A χ 2 goodness‐of‐fit test indicated a significant difference between the three habitat types ( p  = .007, χ 2  = 10.005, df  = 2). While the habitat seems to impact the frequency of infection, Bertiella was not observed to select for other factors such as age or sex of the primate host. Here we identified a significant increase in the frequency of Bertiella infection in an urban environment, which can then be further transmitted to new hosts with more direct primate contact. Bertiella infection has already been documented in humans in Paraguay, all of which were associated with close primate contact. As howlers move into more urban habitats due to urbanization and habitat fragmentation, Bertiella could be introduced into this new ecosystem and has the potential to cause further infections in humans. Abstract : Adult male urban howler monkey in Pilar defecating and urinating. Proglottids of Bertiella sp. are shed through feces. Once in the environment, the eggs can be taken up by mites, which serve as intermediate hosts, and can consequently infect primates, small mammals, or humans. This individual was from the urban habitat, which could put humans in contact with howler feces at greater risk of infection. Research Highlights: Infections of the cestode Bertiella sp. are found in significantly higher percentages in Paraguayan howler monkeys ( Alouatta caraya ) living in an urban habitat compared to their natural habitat. The chance of Bertiella infection was not affected by age or sex of the individual.